2016
DOI: 10.1016/j.celrep.2016.09.093
|View full text |Cite
|
Sign up to set email alerts
|

A Gata2-Dependent Transcription Network Regulates Uterine Progesterone Responsiveness and Endometrial Function

Abstract: SUMMARY Altered progesterone responsiveness leads to female infertility and cancer, but underlying mechanisms remain unclear. Mice with uterine-specific ablation of Gata2 are infertile showing failures in embryo implantation, endometrial decidualization and uninhibited estrogen signaling. Gata2 deficiency results in reduced progesterone receptor (PGR) expression and attenuated progesterone signaling, as evidenced by genome-wide expression profiling and chromatin immunoprecipitation. GATA2 not only occupies at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 45 publications
5
114
0
2
Order By: Relevance
“…Most of the other TFs identified herein are not studied in the development of uterine epithelia. We found that Gata2 (Rubel et al., 2012, Rubel et al., 2016) was uniquely expressed by P14 cells. Immunocytochemistry was performed to confirm the expression of GATA2 at the protein level, with the results showing the highest expression of GATA2 protein in the P14 cells, with particularly strong expression in the cell nuclei (Figure 3B).
Figure 3Molecular Cascades Regulating the Development and Maturation of Uterine Epithelia(A) Differentially expressed transcription factors (TFs) of the respective cell cluster were selected and visualized using a heatmap.(B) Expression of GATA2 protein in uterine epithelia (CD326 + ) during development.
…”
Section: Resultsmentioning
confidence: 99%
“…Most of the other TFs identified herein are not studied in the development of uterine epithelia. We found that Gata2 (Rubel et al., 2012, Rubel et al., 2016) was uniquely expressed by P14 cells. Immunocytochemistry was performed to confirm the expression of GATA2 at the protein level, with the results showing the highest expression of GATA2 protein in the P14 cells, with particularly strong expression in the cell nuclei (Figure 3B).
Figure 3Molecular Cascades Regulating the Development and Maturation of Uterine Epithelia(A) Differentially expressed transcription factors (TFs) of the respective cell cluster were selected and visualized using a heatmap.(B) Expression of GATA2 protein in uterine epithelia (CD326 + ) during development.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, new gene editing technology, such as CRISPR/Cas9 system has opened a new era for the generation of transgenic animal models in a more efficient and economical way that can help further identify uterine-specific enhancer or promoter regions of these PGR-associated genes. For example, PGR and GATA2 both occupy at putative enhancers of the Sox17 and Ihh genes [45] that have pivotal uterine functions [54, 91, 92]. While results from in vitro assays suggest a cooperation of PGR and GATA2 in the regulation of enhancers for the Sox17 and Ihh genes, the in vivo function of such enhancers remains to be demonstrated, perhaps by CRISPR technology.…”
Section: Discussionmentioning
confidence: 99%
“…While results from in vitro assays suggest a cooperation of PGR and GATA2 in the regulation of enhancers for the Sox17 and Ihh genes, the in vivo function of such enhancers remains to be demonstrated, perhaps by CRISPR technology. Furthermore, advanced statistical and bioinformatics tools are available for integrated analysis of genome-wide data from both human subjects and mouse models, which can help to identify genetic networks and regulatory mechanisms that are conserved across species [45, 9395]. Importantly, mapping out evolutionary conservation and difference on regulatory pathways would help better interpretation on data generated from preclinical investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations